ANALISIS IMPLEMENTASI SAK ETAP PADA KOPERASI DI KOTA MATARAM - Baiq Nada Fatimatus Shafira Shafira; Elin Erlina Sasanti; Zuhrotul Isnaini (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2022)
This study aims to analyze the application of Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) in the preparation of cooperative financial statements in Mataram City. The research approach used is a qualitative descriptive approach that compares the preparation and presentation of financial statements in cooperatives with the provisions contained in SAK ETAP. The data analysis technique was carried out by describing the data found in cooperatives and comparing them with SAK ETAP as a guide in preparing and presenting financial reports. The results showed that the Syariah Sepakat Sejahtera Cooperative and the Dharma Sari Bumi Pagutan Savings and Loan Cooperative were still in the development stage in implementing the provisions contained in SAK ETAP.